The contemporary transformation of american youth: an analysis of change in the prevalence of delinquency, 1991-2015 - Baumer, Eric P. (Criminology, 2021)
Youth involvement in crime has declined substantially over the past few decades, yet the reasons for this trend remain unclear. We advance the literature by examining the role of several potentially important shifts in individual attitudes and behaviors that may help to account for the observed temporal variation in youth delinquency. Our multilevel analysis of repeated cross-sectional data from eighth and tenth grade students in the Monitoring the Future (MTF) study indicates that changes in youth offending prevalence were not associated with changes in youth attachment and commitment to school, community involvement, or parental supervision after school. In contrast, the study provides suggestive evidence that the significant reduction in youth offending prevalence observed since the early 1990s was significantly associated with a decrease in unstructured socializing and alcohol consumption and, to a lesser extent, with a decrease in youth preferences for risky activities. Implications for existing theoretical explanations and future research on youth crime trends are discussed.